(untitled) (Journal of Fatima Jinnah Medical University, 2023)
Background: Chronic diseases are considered as added risk of severity of COVID-19 infection. This study was planned to assess practices and fears of patients with chronic diseases during COVID-19 pandemic. Participants and Methods: An online questionnaire was developed and shared with potential participants using the snowball technique. The questionnaire included questions about sociodemographic characteristics, practices and fears related to COVID-19. A total of 181 patients with chronic diseases filled the questionnaire. Results: About 72.4% reported fear due to increased risk of severe COVID-19 infection. Male, married and those living with two or more chronic diseases were more panic as compared to others. About 56% were worried about emergency care for their existing condition. Conclusion: The analysis showed good practices especially wearing a mask and avoiding crowded places among patients with chronic diseases. However, the presence of fear of the severe infection and emergency care might affect their mental health which needs attention and counseling.